Distribution of Inheritance According to Customary Law and Civil Law in Indonesia - Raihana Jihan Sabhira Keliat; Tamaulina Br Sembiring (Ipso Jure, 2024)
This research aims to analyze the distribution of inheritance according to customary law and civil law in Indonesia, considering that this process involves complex financial, emotional and social aspects. In Indonesia, each region has customs that complement its cultural diversity, and the interaction between customary law and civil law in the inheritance distribution process shows unique and often complex dynamics. In this context, civil law plays a vital role in creating a just and prosperous society. In contrast, customary law is deeply related to ways of life developed, shared and passed down from generation to generation. Through a qualitative approach, this research will use case studies from various regions in Indonesia to illustrate the application of inheritance law, and interviews with legal experts, traditional leaders and community members will provide in-depth insight into the interactions between civil and customary law. In addition, analysis of legal documents and jurisprudence will offer a more structured understanding of the basis of statutory law. It is hoped that this research will not only add to academic discourse but also offer practical insights and guidance that can improve legal practices and outcomes in Indonesia's diverse cultural landscape, with the ultimate goal of making policy recommendations for policymakers to improve legal practices around heritage, respecting cultural practices while promoting justice and equality.